Zi ran yu yan chu li shi zhan : cong ru men dao xiang mu shi jian = Practical natural language processing - Sowmya V. B.; Majumder, Bodhisattwa; Gupta, Anju; Surana, Harshit (Ren min you dian chu ban she = Posts & Telecom Press, 2022)
Detailed summary in vernacular field only.